Pre-schoolers with autism : an education and skills training programme for parents : manual for parents - Brereton, Avril V. (Avril Vaux), 1954- (Jessica Kingsley, 2005)
This ground-breaking training programme has been developed in response to a real need for evidence-based early interventions for very young autistic children. Authoritative and extensively tried and tested, it will help both parents and carers to understand the disorder and how it affects child development. Ultimately, the programme is designed to reduce the severity of emotional/behavioural difficulties by managing a child's particular problems and encouraging effective collaboration between professionals and parents. The programme is delivered through two accessible manuals - one for parents.